Tuning the Immunostimulation Properties of Cationic Lipid Nanocarriers for Nucleic Acid Delivery - Dey, Arindam K.; Nougarède, Adrien; Clément, Flora; Fournier, Carole; Jouvin-Marche, Evelyne; Escudé, Marie; Jary, Dorothée; Navarro, Fabrice P.; Marche, Patrice N. (Frontiers in Immunology, 2021)
Nonviral systems, such as lipid nanoparticles, have emerged as reliable methods to enable nucleic acid intracellular delivery. The use of cationic lipids in various formulations of lipid nanoparticles enables the formation of complexes with nucleic acid cargo and facilitates their uptake by target cells. However, due to their small size and highly charged nature, these nanocarrier systems can interact in vivo with antigen-presenting cells (APCs), such as dendritic cells (DCs) and macrophages. As this might prove to be a safety concern for developing therapies based on lipid nanocarriers, we sought to understand how they could affect the physiology of APCs. In the present study, we investigate the cellular and metabolic response of primary macrophages or DCs exposed to the neutral or cationic variant of the same lipid nanoparticle formulation. We demonstrate that macrophages are the cells affected most significantly and that the cationic nanocarrier has a substantial impact on their physiology, depending on the positive surface charge. Our study provides a first model explaining the impact of charged lipid materials on immune cells and demonstrates that the primary adverse effects observed can be prevented by fine-tuning the load of nucleic acid cargo. Finally, we bring rationale to calibrate the nucleic acid load of cationic lipid nanocarriers depending on whether immunostimulation is desirable with the intended therapeutic application, for instance, gene delivery or messenger RNA vaccines.